Enhancement of bactericidal effects of sodium hypochlorite in chiller water with food additive grade calcium hydroxide - TOYOFUKU, Chiharu (J Vet Med Sci, 2017)
An alkaline agent, namely food additive grade calcium hydroxide (FdCa(OH)(2)) in solution at 0.17%, was evaluated for its bactericidal efficacies in chiller water with sodium hypochlorite (NaOCl) at a concentration of 200 ppm total residual chlorine. Without organic material presence, NaOCl could inactivate Salmonella Infantis and Escherichia coli within 5 sec, but in the presence of fetal bovine serum (FBS) at 0.5%, the bactericidal effects of NaOCl were diminished completely. FdCa(OH)(2) solution required 3 min to inactivate bacteria with or without 5% FBS. When NaOCl and FdCa(OH)(2) were mixed at the final concentration of 200 ppm and 0.17%, respectively, the mixed solution could inactivate bacteria at acceptable level (10(3) reduction of bacterial titer) within 30 sec in the presence of 0.5% FBS. The mixed solution also inhibited cross-contamination with S. Infantis or E. coli on chicken meats. It was confirmed and elucidated that FdCa(OH)(2) has a synergistic effect together with NaOCl for inactivating microorganisms.